Pengaruh Defisit Anggaran, Foreign Direct Investment, dan Indeks Pembangunan Manusia terhadap Pertumbuhan Ekonomi ASEAN-5: Asean-5 (Indonesia, Malaysia, Thailand, Filipina, dan Vietnam) - Ariski Aria Admaja; Marissa, Feny; Bashir, Abdul (Fakultas Ekonomi dan Bisnis, Universitas Pembangunan Nasional Veteran Jakarta, 2025)
Purpose: This study aims to analyze the effects of budget deficit, foreign direct investment (FDI), and the Human Development Index (HDI) on economic growth in the ASEAN-5 countries (Indonesia, Malaysia, Thailand, Vietnam, and the Philippines). Design/methodology/approach: The study employs secondary data covering the period 2014–2023 and applies panel data regression methods. The estimation is conducted using the Fixed Effect Model (FEM) to examine the impact of the independent variables on economic growth. Findings: The results indicate that budget deficit, FDI, and HDI, both individually and simultaneously, have a positive and significant effect on economic growth in the ASEAN-5 region. Research limitations/implications: The study is limited to the 2014–2023 period and only covers five ASEAN countries; therefore, the findings cannot be generalized to the entire Southeast Asian region. Future research is recommended to expand the variables and country coverage to gain a more comprehensive understanding. Practical implications: The findings highlight the importance of effective fiscal policies, the promotion of a competitive investment climate, and the development of human resources as key strategies for sustainable development in ASEAN. Paper type: Research paper Keywords: Economic Growth; Budget Deficit; Foreign Direct Investment; Human Development Index.